2008
DOI: 10.2967/jnumed.107.047704
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed Improves Tumor Selectivity of 111In-DTPA-Folate in Mice with Folate Receptor–Positive Ovarian Cancer

Abstract: Folate-based radiopharmaceuticals can be used as imaging agents and for potential radiotherapy of folate receptor (FR)-positive malignant tissue (e.g., ovarian carcinomas). However, substantial FR expression in the kidneys results in undesired renal retention of radioactivity. Recently, we found that the preinjection of an antifolate significantly improved tumor selectivity of organometallic 99m Tc-radiofolates in mice. The aim of this study was to corroborate the effect of pemetrexed with the clinically teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 26 publications
7
60
1
Order By: Relevance
“…The biodistribution profiles of acetazolamide derivatives compares favourably with the ones previously reported for other ligands [23][24][25][26]. In particular, we were pleased to see that %ID/g values in the tumor were higher than the corresponding values in the kidney (the main organ for drug clearance), even as early as one hour after intravenous administration of the product [18].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The biodistribution profiles of acetazolamide derivatives compares favourably with the ones previously reported for other ligands [23][24][25][26]. In particular, we were pleased to see that %ID/g values in the tumor were higher than the corresponding values in the kidney (the main organ for drug clearance), even as early as one hour after intravenous administration of the product [18].…”
Section: Discussionsupporting
confidence: 62%
“…Unlike antibodies (which can easily be raised against the majority of target proteins of interest), it is not always easy to generate high-affinity small molecule ligands to tumor-associated antigens. However, excellent tumor-targeting results have been reported for folate analogues targeting folate-receptor positive tumors [23,24], substituted urea derivatives targeting prostate-specific membrane antigen [25], somatostatin antagonists targeting the somatostatin receptor [26] and for carbonic anhydrase IX (CAIX) ligands [16][17][18]27].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence there is an inherent risk of damage to the kidneys by particle radiation. However, we have shown in several preclinical studies that administration of the antifolate pemetrexed (PMX) resulted in a tremendous reduction of the radiofolate's retention in the kidneys whereas accumulation in tumor xenografts remained unaffected (11)(12)(13). The exact mechanism of this interaction is still not completely clear.…”
Section: Introductionmentioning
confidence: 97%
“…IGROV-1 cells are human ovarian cancer cells that express the folate receptor at a somewhat lower level than KB cells (12,31,36). The human prostate cancer cell line PC-3 does not express the folate receptor and was used as a negative control.…”
Section: Cancer Cell Linesmentioning
confidence: 99%
“…Recently, Müller et al reported a favorable effect of the antifolate pemetrexed on kidney and tumor uptake (17,18); thus, the high radioactivity accumulation and the potential risk of damage to the kidneys may no longer be an issue.…”
mentioning
confidence: 99%